‘Are you going to go?’ Putting a pedagogical grammar rule under the corpus spotlight - BURTON, GRAHAM (Glottodidactica, 2021)
A rule stating that we tend to avoid using go and come after the future marker going to appears again and again in many coursebooks and grammars used in English Language Teaching, and has done for decades. This article attempts to show, using empirical evidence from corpora, why the rule is inaccurate, and different ways that this might be established. As the rule under consideration is typically framed as a tendency (like many other pedagogical grammar rules), an additional aim of the work is to outline the kinds of corpus analyses researchers and materials designers can potentially use in order to investigate the question of (claimed) linguistic tendencies. The article concludes by discussing why a rule that is apparently inaccurate nevertheless appears again and again in print, arguing that the existence of a well-established and widely-accepted ‘canon’ of ELT grammar means that such inaccuracies in descriptions of grammar can be easily perpetuated